Popular Protest in East Germany : Revolution. - Dale, Gareth (Taylor & Francis Ltd., 2005)
"Popular Protest in the East German Revolution"is a study of dissent and protest in the German Democratic Republic, focusing on the upheaval of 1989-1990.